1999
DOI: 10.1046/j.1365-2133.1999.02661.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of anxiety and dermatology life quality in patients with atopic dermatitis

Abstract: Anxiety is a prevalent psychological factor associated with atopic dermatitis (AD). AD patients generally suffer from a high anxiety level, and psychological treatment documents a positive effect on the anxiety level, as well as the course and management of the disease. The Dermatology Life Quality Index (DLQI) has been suggested as a relevant clinical measure in AD. This study investigated the relationship between the severity of AD, dermatological life quality and anxiety. Thirty-two adults suffering from AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
116
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(139 citation statements)
references
References 11 publications
16
116
0
7
Order By: Relevance
“…However, we found no statistically significant differences in anxiety between men and the women in the group of patients with atopic dermatitis. Similarly, Linnet and Jemec (1999) found that there were no differences between genders in the group of patients with atopic dermatitis. An interesting finding is that the incidence of anxiety in women in the group of patients with acne was twice as high as in women in the group of patients with atopic dermatitis.Levels of depression were almost the same in men and women in both groups, which does not confirm findings by other authors (Gupta et al, 1994;Picardi et al, 2004) who found that there was higher depression and other mental health problems in women, since they perceive situations and events more emotionally than men.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…However, we found no statistically significant differences in anxiety between men and the women in the group of patients with atopic dermatitis. Similarly, Linnet and Jemec (1999) found that there were no differences between genders in the group of patients with atopic dermatitis. An interesting finding is that the incidence of anxiety in women in the group of patients with acne was twice as high as in women in the group of patients with atopic dermatitis.Levels of depression were almost the same in men and women in both groups, which does not confirm findings by other authors (Gupta et al, 1994;Picardi et al, 2004) who found that there was higher depression and other mental health problems in women, since they perceive situations and events more emotionally than men.…”
Section: Discussionmentioning
confidence: 84%
“…The effects on quality of life in patients with acne have been stated in several studies (Do et al, 2009;Tasoula et al, 2012;Yap, 2012;El-Khateeb et al, 2014). Quality of life affected by atopic dermatitis has also been described by several authors (Linnet, Jemec, 1999;Turčeková, 2012). As there are differences between men and women in the experience of emotions, in the next part of the study we studied differences in anxiety, depression, and quality of life between genders in both groups of patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A relação entre variáveis demográficas, fatores psicológicos, manifestações clínicas da DA tem sido investigada em vários estudos da literatura internacional (Linnet, Jemec, 1999;Kurwa, Finlay 1995;Eun, Finlay et al, 1990). No Brasil, não há estudos publicados que correlacionam a qualidade de vida e a DA de pacientes adultos.…”
Section: -Introduçãounclassified